UMPSA Sustainable Mobility Expedition spreads goodwill in Songkhla - Siti Nur Azwin, Zulkapri (UMPSA, 2024)
SONGKHLA, THAILAND, 18 February 2024 - A total of 85 volunteer staff and students from Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) extended assistance to orphaned and underprivileged students at the Bumrungsuksa Islamic Boarding School (BIS), Hatyai Songkhla, Thailand recently.